N-Oxide Coordination to Mn(III) Chloride - Ananya Saju; Matthew R. Crawley; Samantha N. MacMillan; Pierre Le Magueres; Mark Del Campo; David C. Lacy (Molecules)
We report on the synthesis and characterization of Mn(III) chloride (MnIIICl3) complexes coordinated with N-oxide ylide ligands, namely trimethyl-N-oxide (Me3NO) and pyridine-N-oxide (PyNO). The compounds are reactive and, while isolable in the solid-state at room temperature, readily decompose into Mn(II). For example, “[MnIIICl3(ONMe3)n]” decomposes into the 2D polymeric network compound complex salt [MnII(µ-Cl)3MnII(µ-ONMe3)]n[MnII(µ-Cl)3]n·(Me3NO·HCl)3n (4). The reaction of MnIIICl3 with PyNO forms varied Mn(III) compounds with PyNO coordination and these react with hexamethylbenzene (HMB) to form the chlorinated organic product 1-cloromethyl-2,3,4,5,6-pentamethylbenzene (8). In contrast to N-oxide coordination to Mn(III), the reaction between [MnIIICl3(OPPh3)2] and 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO) resulted in electron transfer-forming d5 manganate of the [TEMPO] cation instead of TEMPO–Mn(III) adducts. The reactivity affected by N-oxide coordination is discussed through comparisons with other L–MnIIICl3 complexes within the context of reduction potential.